IN SITU RECOVERY & REMEDIATION OF METALS - DRUMMOND EARLEY III (Society FOR MINING, METAL, 2020)
This book provides a state-of-the-art synopsis of in situ metal recovery and remediation technologies based on both research and commercial projects. In situ recovery uses fluid-based metal dissolution and recovery to extract one or more commodities from a largely intact rock mass using similar processes that create ore deposits.